María García, Clori, la actriz bonapartista - Fernando Doménech Rico (Cuadernos de Ilustración y Romanticismo)
María García, whom Moratín celebrated in his verses under the name of Clori, was the most relevant actress in Madrid during the reign of José Bonaparte. First lady of Máiquez’s company, she stood out by her beauty, her liveliness and the sensitivity that she displayed in the many roles she played. She left Madrid in 1812 with Moratín and the mayor García de la Prada, whom she married. She died in 1826 without having returned to the stage.